Optimization of Human Resource Development: Analyzing Differences in Job Satisfaction Based on Diversity of Positions, Employee Status and Generations at the Artificial Insemination Center - Fitri Hidayah, Ratna; Sunaryo, Hadi; Sudaryanti, Dwiyani (Riviera Publishing, 2024)
The Singosari Artificial Insemination Center (BBIB) is a Technical Implementation Unit (UPT) under the Ministry of Agriculture that has implemented the Financial Management Pattern of the Public Service Agency with the task and function of providing public services to all stakeholders, both direct and indirect. Employee performance can be affected by job satisfaction, however, so far there has been no analysis of the level of employee job satisfaction. This study aims to analyze the level of employee job satisfaction and to find out the difference in employee job satisfaction based on the diversity of positions, employee statuses and generations. This research is a mixed research (Mix methods) conducted at BBIB Singosari, Malang Regency, East Java. using an instrument in the form of a questionnaire which was distributed to 142 respondents using the census sampling technique. This study uses descriptive analysis in the form of factor analysis and inferential analysis in the form of the Mann Whitney Test and the Kruskal Wallis Test. With the findings of seven dimensions of job satisfaction, namely the job itself, leadership, colleagues, job promotions, work facilities and work environment are in the high category and have the same job satisfaction category, which is quite satisfied on average. One indicator with a low score is an allowance indicator and there is a significant difference in job satisfaction based on position and generation, but there is a non-significant difference in job satisfaction between civil servants and non-civil servants. It is hoped that BBIB Singosari will always socialize and maintain transparency regarding the compensation structure for non-civil servant employees, including how wages and incentives are determined and distributed. Acknowledging the differences in job security and benefits between civil servants and non-civil servants. As well as considering the desires and expectations between generations.